Vom Staunen der Vernunft - Pareyson, Luigi (Studien zur systematischen Theologie, Ethik und Philosophie, 2021)
Luigi Pareyson has so far been little known in the German-speaking world, although his works have been translated into many languages, as he is undoubtedly one of the founders of modern philosophical hermeneutics, along with Hans-Georg Gadamer and Paul Ricoeur. Because of his intellectual diversity, he has inspired many of his students, who include Umberto Eco and Gianni Vattimo, and opened up to them a broad spectrum ranging from idealist approaches to hermeneutics and aesthetic theory. The volume provides a diverse but at the same time coherent sketch of important motifs of his philosophy: the main features of his interpretation of Fichte and Schelling, the foundations of his "ontology of freedom," his philosophical hermeneutics of religious experience, the basic lines of his aesthetics, and finally considerations concerning the social function that philosophy would have. Like a common thread, an intellectual attitude of wonder runs through all these contributions. It is the attitude of not fully comprehending human existence and its freedom, the evil in history, the phenomenon of exuberant beauty, the interpretive power of myth, the inevitable otherness of the other and of the self itself. And it is precisely this astonishment that has led people - from the beginning until today - to philosophize.